P123 Chemotherapy response score predicts surgical outcome and prognosis in tubo-ovarian cancer. (1st November 2019) - Dasgupta, A; Gomes, N; Blake, D; Kucukmetin, A
Abstract : Introduction/Background: Bohm's 3 tier CRS is a histopathological score for assessing tumour regression in omentectomy specimens after neoadjuvant chemotherapy(NACT).Bohm et al has concluded that CRS is more important prognostic factor than completeness of cytoreduction(CC) in IDS, but this has not been proved by other validation studies. There is a conflict in evidence regarding improvement of overall survival (OS) with CRS-3 in available literature( Bohm et al, Coghlan et al, Lee et al no significant difference vs significant difference-Rajkumar et al ). Evidence of association of CRS with radiological and biochemical(CA-125 decline) response is lacking and conflicting. Methodology: Patients who underwent IDS between 2010 and 2017 at NGOC were retrospectively analysed. Omental disease was scored by pathologists as per CRS reporting system described by Bohm. Surgical end result and clinico-pathological data was collected and correlated with CRS. Recurrence was assessed radiologically, OS and progression free survival (PFS) calculated in the 3 histopathological sub-groups, and compared with clinical variables using Cox proportional hazard model and log-rank test. Results: 201 patients who underwent IDS were included in the analysis(table 1). CC was possible in 35 patients with CRS-3(65%) vs 24 patients in CRS-2(37%) and 18 patients in CRS-1(22%)(p<0.0001), and this is seen after adjusting for stage(stage IV B-2 sided p:0.02, for stage IIIC, p=0.0012). Significant increase in PFS in patients with CRS 3 vs CRS1+2(log rank test for trend;χ 2 :41.75, HR:2.8, p<0.0001) as well as in OS in patients with CRS3 vs CRS1+2(χ 2 :28.4, HR:2.6, p<0.0001) Biochemical response(CA-125 decline after NACT) and radiological response were predictors of chemotherapy response scores. Conclusion: CRS is an independent prognostic factor and a post NACT pre-IDS omental biopsy may help predict completeness of surgery at IDS and overall good prognosis. Future prospective trials will be useful to identify and understand whether CRS-3 tumours are a different disease entity. Disclosure: Nothing to disclose.